Recurrent, bilateral endogenous Candida endophthalmitis with multiple focal chorioretinal lesions: management with pars plana vitrectomy and focal endolaser - Prashanth G. Iyer; Jason Fan; J. Daniel Diaz; Jeremy Liu; Thomas Lazzarini; Kenneth C. Fan; Darleen Miller; Harry W. Flynn (Journal of Ophthalmic Inflammation and Infection, 2022)
Abstract Purpose Bilateral endogenous Candida endophthalmitis (ECE) treatment usually involves administering systemic and intravitreal antifungal medications. In advanced cases with vitreous seeding, pars plana vitrectomy (PPV) is considered. The use of focal endolaser treatment to chorioretinal lesions has not been reported. We present a case of bilateral recurrent ECE treated with PPV and endolaser to elevated focal lesions. Case A 45-year-old diabetic male presented with decreased visual acuity in both eyes (20/50 right eye, 20/150 left eye) and was found to have bilateral ECE with moderate vitritis and chorioretinal lesions. The initial treatment consisted of multiple intravitreal voriconazole injections to both eyes as well as systemic antifungal therapy. Resolution of ECE occurred after three months, but one year later despite therapy recurred bilaterally. Patient underwent PPV with endolaser to the elevated chorioretinal lesions in both eyes. One year later, his vision improved to 20/40 in both eyes, focal lesions were flat and resolved along with the ECE. Conclusion Advanced or recurrent ECE that is refractive to intravitreal antifungal therapy may be treated with PPV. Endolaser therapy to the chorioretinal lesions is an additional local option that can resolve the activity of ECE.